Modernity, Nation and Urban-Architectural Form The Dynamics and Dialectics of National Identity vs Regionalism in a Tropical City (Springer International Publishing, 2018)
This book explores how Malaysia, as a multicultural modern nation, has approached issues of nationalism and regionalism in terms of physical expression of the built environment. Ever since the nation's post-Colonial era, architects and policy makers have grappled with the theoretical and practical outcomes of creating public architecture that effectively responds to traditions, nationhood and modernity. The authors compile and analyse prevailing ideas and strategies, present case studies in architectural language and form, and introduce the reader to tensions arising between a nationalist agenda and local 'regionalist' architectural language. These dichotomies represent the very nature of multicultural societies and issues with identity; a challenge that various nations across the globe face in a changing environment. This topical and pertinent volume will appeal to students and scholars of urban planning, architecture and the modern city.